A Modern Approach to the Accuracy of Assessment of Mathematical Creative Thinking Ability of Junior High School Students Through Graded Response Models - Kurniawan, Novi; Mujahidawati, Mujahidawati; Falani, Ilham (FKIP - Universitas Riau, 2025)
The ability to think creatively in mathematics is a crucial aspect that must be possessed by students, so that they can face the dynamics of change and challenges in life that continues to develop. Graded Response Models (GRM) is one of the models of the modern approach of Item Response Theory (IRT) to polytomus data. Graded Response Models (GRM) are used to estimate students' test item ability and mathematical creative thinking skills. This research is a type of quantitative research with an ex post facto method. This study uses the responses of Junior High School (SMP) Class VIII students in the North Bahar sub-district, Muaro Jambi Regency. A total of 120 grade VIII students spread across 4 State Junior High Schools in the sub-district were the subjects of this study. The instrument used was a test instrument for students' mathematical creative thinking skills amounting to 2 questions with each question having 4 indicators of mathematical creative thinking ability. The data was analyzed using the GRM approach using the help of Parscale 4.1 software. Based on the results of data analysis, the results of estimating the ability parameter (θ) of mathematical creative thinking are mostly at medium ability. This can be seen from the histogram of the results of estimating the parameters of mathematical creative thinking ability, most students are in the range of -1 to 1.